Human resource aspect of agricultural economy – challenges of demographic change - Rajczi, Alexandra; Vörös, Péter; Dajnoki, Krisztina (Applied Studies in Agribusiness and Commerce, 2017)
Over the past decades, the agrarian policy has tried to contribute to the catching-up of the rural areas with varying dynamism and aid scheme. However, its result is significantly below expectations. Nowadays, the age composition of the population living in rural areas reveals an unfavourable picture; the rate of the elderly, deprived persons and people being inactive from the aspect of employment is high and it is also combined with the low educational levels. The young generations and intellectuals leave the rural areas and, consequently, the rate of the active population continues to grow narrow as well as the proportion of young and skilled employees decreases. As a consequence of changes in the past decades, the rate of agricultural employment has not led to an intensive change but a failing change in extensive direction which lays off jobs. Nowadays, this process also determines the Hungarian rural society. In the sector, the need for employment diminishes as a result of the development in technology and due to the expansion of services sector. The purpose of our study is to present and analyse the human resources of our country’s agriculture by skill level and age group and compare it with the needs of companies, by doing this we try to compare supply and demand. In details, based on secondary data source, we investigate the agricultural labour force and try to confront it with the advertisements of job search portals (three of our job search portals based on our predefined criteria), by which we achieve a current picture of the agricultural human resource circumstances.JEL Code: J43